2023
DOI: 10.1111/febs.16749
|View full text |Cite|
|
Sign up to set email alerts
|

Linear ubiquitination improves NFAT1 protein stability and facilitates NFAT1 signalling in Kawasaki disease

Abstract: NFAT1 is known for its roles in T cell development and activation. So far, the phosphorylation of NFAT1 has been extensively studied, but the other post‐translational modifications of NFAT1 remain largely unknown. In this study, we reported that NFAT1 is a linearly ubiquitinated substrate of linear ubiquitin chain assembly complex (LUBAC). LUBAC promoted NFAT1 linear ubiquitination, which in turn inhibited K48‐linked polyubiquitination of NFAT1 and therefore increased NFAT1 protein stability. Interestingly, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Finally, we recommend looking into a recently published research article by Ying Miao et al . [19] that revealed a biological function for linear ubiquitination of NFAT1, a factor involved in developmental pathways, in Kawasaki disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we recommend looking into a recently published research article by Ying Miao et al . [19] that revealed a biological function for linear ubiquitination of NFAT1, a factor involved in developmental pathways, in Kawasaki disease.…”
Section: Discussionmentioning
confidence: 99%
“…We also invite our readers to read The FEBS Journal articles published in the last couple of years that are linked to the theme of developmental pathways in disease (and which are not included in this Collection); these involve, among others, an overview of the role of Notch signaling in development and disease [16], a summary of the impact of serine pseudoproteases on physiology and pathology [17], and also a review of the developmental processes involved in wound repair [18]. Finally, we recommend looking into a recently published research article by Ying Miao et al [19] that revealed a biological function for linear ubiquitination of NFAT1, a factor involved in developmental pathways, in Kawasaki disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, a cycloheximide chase experiment revealed enhanced NFAT1 degradation in the absence of HOIP, which can be prevented by proteasome inhibitors [7]. Miao et al [7] next demonstrate that LUBAC-mediated linear ubiquitination prevents degradative K48-linked ubiquitination of NFAT1, promoting nuclear translocation of NFAT1 and subsequent increase in target gene expression (Fig. 1).…”
Section: Novel Role For Linear Ubiquitination In Protein Stabilisationmentioning
confidence: 93%
“…Interestingly, the authors noticed that overexpression of LUBAC components increases co-expression of NFAT1, while knock-down of HOIP has an opposite effect, which could not be linked to the changes in the Nfatc2 (NFAT1) mRNA levels. However, a cycloheximide chase experiment revealed enhanced NFAT1 degradation in the absence of HOIP, which can be prevented by proteasome inhibitors [7]. Miao et al [7] next demonstrate that LUBAC-mediated linear ubiquitination prevents degradative K48-linked ubiquitination of NFAT1, promoting nuclear translocation of NFAT1 and subsequent increase in target gene expression (Fig.…”
Section: Novel Role For Linear Ubiquitination In Protein Stabilisationmentioning
confidence: 95%
See 1 more Smart Citation